Determinantes do gasto legislativo municipal: uma análise com base nos municípios do Estado de São Paulo no período 1997-2010 - Gumier, Alessandro Elias (2013)
Public spending has gained increasing relevance in the economic analysis. However, few studies have dealt with the public expense of the legislative branch. The goal of this dissertation is to analyze legislative spending of São Paulo cities between 1997-2010, as well as estimate the socioeconomic points for the level of this expense. Thereby, we used the methodology of cluster analysis and linear regression in cross-section of socioeconomic factors of the 645 counties, based on 2010 data. The results suggest that the number of councilors is not clearly relevant factor to explain the legislative municipal spending, pointing out, however, the municipal income as the most significant variable for the occurrence of this sort of expense